Embrace : God's radical shalom for a divided world - Barber, Leroy (IVP Books, an imprint of InterVarsity Press, 2016)
The walls between us seem impenetrable. We live in an age of strife and division. Factors such as race, class, values and lifestyles keep us from connecting with others in meaningful ways. It's easy to avoid or ignore those who make us uncomfortable and those we simply do not like, but God's call to the church is to do just the opposite. Leroy Barber has spent decades pursuing reconciliation and justice amongst groups of vastly diverse people. He knows the challenge of embracing those who are difficult to embrace, yet he advocates that the way to radical shalom on earth is through pursuing these relationships. We have the opportunity as the people of God to bring true peace and unity to a world that desperately needs it. Embrace the challenge to show a divided world the bridge-building power of God's love.